2009
DOI: 10.1111/j.1365-2222.2008.03167.x
|View full text |Cite
|
Sign up to set email alerts
|

EpidemAAITO: Features of food allergy in Italian adults attending allergy clinics: a multi‐centre study

Abstract: Plant-derived foods cause most food allergies in Italian adults. The pollen-food allergy syndrome is the most frequent type of food allergy followed by allergy to LTP whose frequency increases southbound. The pattern of allergy to certain foods is clearly influenced by specific geographic features such as pollen exposure and dietary habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
2
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 28 publications
7
121
2
8
Order By: Relevance
“…Fresh fruit was an important trigger of anaphylaxis, both in adults and in children, peach being the most frequent one, followed by apple. Plant-derived foods, due to lipid transfer protein (LTP) sensitization, are the most important cause of type 1 food allergy in Italy, according to a recent epidemiological survey [22] and in agreement with what is observed in the Mediterranean countries [23]. In our study, food anaphylaxis was more commonly observed in boys than in girls, but this gender preference reverses in adulthood, where it was more commonly observed in female than in male patients.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Fresh fruit was an important trigger of anaphylaxis, both in adults and in children, peach being the most frequent one, followed by apple. Plant-derived foods, due to lipid transfer protein (LTP) sensitization, are the most important cause of type 1 food allergy in Italy, according to a recent epidemiological survey [22] and in agreement with what is observed in the Mediterranean countries [23]. In our study, food anaphylaxis was more commonly observed in boys than in girls, but this gender preference reverses in adulthood, where it was more commonly observed in female than in male patients.…”
Section: Resultssupporting
confidence: 91%
“…A history of asthma appears to be a major risk factor for life-threatening anaphylactic reactions to food [28][29][30], but it is not particularly specific, as about a third of food allergic patients have asthma. Many of our patients (one-third of adults) had the oral allergic syndrome, mainly due to pollen-food allergy, as it is commonly observed in Northern Italy [22]. In conclusion, food is an important cause of anaphylaxis in the general population, particularly in subjects with respiratory allergic comorbidities (rhinitis and asthma).…”
Section: Resultsmentioning
confidence: 54%
“…Non-specific lipid transfer proteins (nsLTPs), particularly peach Pru p 3, are the most important plant food allergens in the Mediterranean area (Asero et al, 2009;Fernandez-Rivas et al, 2003;Salcedo et al, 2007;van Ree, 2002). They constitute a panallergen family of 9 kDa (90-95 amino acids) basic peptides, with a rigid 3D-structure due to the presence of four conserved disulphide bridges .…”
Section: Introductionmentioning
confidence: 99%
“…Despite a low prevalence of buckwheat allergy, it is one of the major foods causing severe life‐threatening reactions 3, 4, 5, 6, 7, 9. As neither skin testing nor the presence of buckwheat‐sIgE proved to be useful for precisely predicting clinical allergy, the diagnosis is still based on a positive food challenge and/or a clear‐cut history of severe reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Two Italian studies reported a sensitization prevalence of 3.6% and a prevalence of buckwheat anaphylaxis of 1%, respectively. In France, the prevalence was 4.5% of cases of food anaphylaxis 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%